A Cross-Sectional Survey of Instagram to Assess Quality and Reliability of Information Regarding Tuberculosis - Rohan Singhal; Nagaspurthy Reddy Anugu (University Library System, University of Pittsburgh, 2024)
Background: Tuberculosis is one of the oldest diseases known to affect humans and a major cause of death worldwide. The National Strategic Plan 2017-2025 aims to eliminate tuberculosis by 2025. Appraising knowledge and awareness of tuberculosis are essential for successful tuberculosis control, given the significance of social and psychological variables in determining health outcomes. Methods: A cross-sectional observational study was conducted wherein, the top six hashtags related to "Tuberculosis" on Instagram, identified by the maximum number of posts were taken. A questionnaire was made for assessment of these posts based on various pre-determined categories- type of post, type of information circulated and to assess if it is "true", "false" or "cannot be determined" using the WHO Factsheet on Tuberculosis & CDC. Result: A total of 370 posts were found to be relevant according to the inclusion criteria and had vast user interaction These posts created and uploaded by the health and wellness industry comprised of 27.02%, followed by doctors at 20.27% and news agencies at 5.96%. 50.54% of the posts analyzed contained a description of tuberculosis and 20% about prevalence and diagnosis The posts by doctors and health and wellness industry had a statistically significant higher number of posts that contained "true" information and scored statistically  significantly higher on the mean of Global Quality Scores and Reliability Scores. Conclusion: Social media is a powerful medium for disseminating scientific facts on TB. The government and policymakers need to develop internet-based programs and interventions to improve knowledge, attitudes, and practices towards TB.